Size optimization of mid-frequency vibro-acoustic systems in the framework of modal energy analysis - Yu, Yang; Wang, Dongping; Zhao, Guozhong; Li, Yonghua; Chen, Bingzhi (Structural and multidisciplinary optimization, 2022)
Modal energy analysis (MODENA) is an energy-based method to compute the pure tone mid-frequency response of a vibro-acoustic system. This method considers frequency-dependent modal energies, input power, dissipated power and transmitted power between the modes of coupled subsystems. The quantities are determined by the basic modal information of the uncoupled subsystems, which also has a close relationship with the structural sizes. The present work addresses developing a size optimization procedure within the framework of MODENA to reduce the mid-frequency acoustic response of vibro-acoustic systems. Via a gradient-based optimization algorithm, the sensitivity of the acoustic energy at pure tone with respect to the structural thickness is deduced by employing a complex variable method. By optimizing the thicknesses on different areas of the structural subsystem given the constraint on total mass, the global energy of the acoustic subsystem is reduced significantly. Furthermore, in an effort to examine the capability of the proposed optimization procedure in dealing with acoustic and aerodynamic excitations encountered in engineering problems, the noise reduction of vibro-acoustic systems under turbulent boundary layer (TBL) pressure fluctuations is investigated. The optimization procedure is demonstrated on a plate/cavity system excited by a point drive and by TBL flow and two kinds of vehicles subject to TBL excitation.